STRATEGI TRANSFORMASI EKONOMI NASIONAL: PENGUATAN KEDAULATAN MELALUI HILIRISASI, KETAHANAN PANGAN, DAN REFORMASI FISKAL MENUJU INDONESIA EMAS 2045 - Fenni Yufantria; Al-Amin (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study examines Indonesia's national economic transformation strategy, which focuses on three main pillars, namely downstreaming, food security, and fiscal reform, as efforts to strengthen economic sovereignty towards the vision of Indonesia Emas 2045. Downstreaming plays a role in increasing the added value of natural resources, reducing dependence on raw material exports, and encouraging the creation of globally competitive domestic industries. Food security is the foundation of social and economic stability, ensuring the availability and affordability of food for all citizens on a sustainable basis. Fiscal reform acts as a pillar that guarantees the availability of development financing, provides strategic incentives, and improves state budget management. This study uses a literature review method by analysing relevant academic sources, policy documents, and case studies. The findings indicate that the synergy among these three pillars can significantly strengthen economic sovereignty, enhance national competitiveness, and accelerate the achievement of inclusive and sustainable development. However, various challenges such as infrastructure gaps, climate change, global economic volatility, and suboptimal governance must be addressed through adaptive, collaborative, and evidence-based policies.